Investigation of the feasibility of including different cryptocurrencies in the investment portfolio for its diversification - Juškaitė, Lina; Gudelytė-Žilinskienė, Laura (Business, Management and Economics Engineering, 2022)
Purpose – the main aim of this article is to identify cryptocurrencies suitable for investment and portfolio diversification. Research methodology – the methodology of empirical research includes methods of scientific literature analysis, statistical data analysis, multicriteria evaluation, correlation analysis. Findings – Bitcoin is the leading cryptocurrency, but this result could have been due to an exceptionally high market capitalization. Based on the results of the analysis, the inclusion of Bitcoin, Etherium and Dogecoin in the investment portfolio of S&P500, Euro Stoxx 50, DAX and CAC 40 indexes could be considered. Terra could be an interesting investment when considering the benefits of diversification. Research limitations – based on the results of the study, the inclusion of all studied cryptocurrencies in the investment portfolio could be considered in order to diversify the portfolio, taking into account their investment attractiveness. Practical implications – Cryptocurrencies attract investors not only because of the returns they receive, but also because of the absence of intermediaries, which allows them to reduce transaction costs. High returns are associated with high risks, so it is necessary to conduct as much research as possible to identify the benefits of cryptocurrencies and to find risk management strategies. One such benefit of cryptocurrencies highlighted in research is diversification. Originality/Value – the novelty of the study lies in evaluation of 10 selected cryptocurrencies according to different criteria using a multi-criteria valuation method to identify cryptocurrencies that are non-correlated or weakly correlated with traditional assets and the most suitable for investment and for portfolio diversification.